Labour rights in trade agreements: Five new stories - Martin Myant (European Trade Union Institute (ETUI), 2022)
Labour provisions in trade agreements have been criticised for minimal effectiveness in improving employment conditions. Five recent cases point to some benefits and to the lessons on when and how labour provisions can be effective. They make a difference in particular economic and political circumstances and when they are a support to an active trade union movement, pressing demands relevant to the country at the time. In Uzbekistan trade sanctions and international pressure were crucial in moves towards the abolition of forced and child labour, but new issues have arisen requiring independent worker representation which does not yet exist. For Vietnam the economic incentive for a trade agreement with the USA plus problems in its industrial relations system led to acceptance of scope for independent trade union activity. Withdrawal of the USA, however, led to a watering down of reforms. A long history of struggle for trade union rights in South Korea was helped by a negative judgement on the government's practices under the free trade agreement with the EU, after which the Korea parliament ratified ILO conventions on free association and collective bargaining. Georgia's quest for international recognition stimulated an extremely liberal employment code associated with gross violations of workers' rights. This was gradually reversed after its Association Agreement with the EU required acceptance of much of EU employment law within a strict timescale. Implementation required political changes within Georgia and the active efforts of Georgian and European trade unions. Mexico is tied to the US economy and US labour was in an exceptionally strong position when President Trump was rushing to win approval for a replacement of the NAFTA agreement. This was approved in the USA after Mexico, under a new government sympathetic to labour, implemented new laws, opening the way for genuine collective bargaining. These included a rapid response mechanism against violations which quickly brought results.
Keywords: 330; Arbeitsrecht; Handelsabkommen; Usbekistan; Vietnam; Südkorea; Georgien; Mexiko